The impact of advertising expenditure on the performance of Islamic banks in Malaysia - Maisyarah Stapah @ Salleh; Nizam Ahmat; Caroline Rosie Jeffrey Nasah (Labuan Faculty of International Finance, Universiti Malaysia Sabah, 2023)
This paper investigates the impact of advertising expenditure on the performance of Islamic banks in Malaysia. A static panel data employed to analyse the data gathered from each Islamic banks annual report over the period of 2008 to 2021. The finding reveals that advertising expenditure (InADT) has significant impact on both Return On Assets (ROA) and Return On Equity (ROE) where the higher the advertising expenditure, the higher the ROA and ROE. Logarithm of the bank net income (lnINC) also has the same significant relationship towards ROA and ROE. On the other hand, logarithm of total financing (InTF) significant only to ROE while logarithm of total costumer deposit (lnDEP) not significant to both ROA and ROE. In conclusion, the Islamic banks need to spend on advertising expenditure to boost its performance. At the same time, the management of the Islamic banks need to carefully plan their advertising strategy based on the segmentation of the customers in order to increase the performance of the Islamic banks. Meanwhile, future study may include macroeconomic variables in the model, investigate the impact of InADT towards conventional banks in Malaysia and examine the long-run impact of advertisement expenditure on the banking performance.